2009
DOI: 10.1017/s1471068409003767
|View full text |Cite
|
Sign up to set email alerts
|

CP-logic: A language of causal probabilistic events and its relation to logic programming

Abstract: We examine the relation between constructive processes and the concept of causality. We observe that causality has an inherent dynamic aspect, i.e., that, in essence, causal information concerns the evolution of a domain over time. Motivated by this observation, we construct a new representation language for causal knowledge, whose semantics is defined explicitly in terms of constructive processes. This is done in a probabilistic context, where the basic steps that make up the process are allowed to have non-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
106
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(106 citation statements)
references
References 39 publications
0
106
0
Order By: Relevance
“…Unfortunately, PGMs are unsuitable for capturing knowledge that goes beyond statistical dependence and independence information, like clinical guidelines. In contrast, it has been shown that CP-logic that the probabilistic verification introduced in this chapter is based upon, can also represent various PGMs [19,39].…”
Section: Probabilistic Verificationmentioning
confidence: 96%
See 2 more Smart Citations
“…Unfortunately, PGMs are unsuitable for capturing knowledge that goes beyond statistical dependence and independence information, like clinical guidelines. In contrast, it has been shown that CP-logic that the probabilistic verification introduced in this chapter is based upon, can also represent various PGMs [19,39].…”
Section: Probabilistic Verificationmentioning
confidence: 96%
“…In [19], the semantics of this CP-logic is presented by relating the set of laws to a possible probabilistic causal process. We briefly introduce the semantics of CPDL in the spirit of CP-logic.…”
Section: Causal Probabilistic Decision Logicmentioning
confidence: 99%
See 1 more Smart Citation
“…It underlies many probabilistic logic programming languages such as Probabilistic Horn Abduction (Poole, 1993), PRISM (Sato, 1995;Sato and Kameya, 2001), Independent Choice Logic (Poole, 1997), Logic Programs with Annotated Disjunctions (Vennekens et al, 2004), ProbLog (De Raedt et al, 2007) and CP-logic (Vennekens et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In this semantic framework, logic programming (LP) is used to define a probability distribution over a set of binary facts. Examples of languages based on that semantics are ProbLog [6], PRISM [7], ICL [8], and CP-logic [9]. The choice for this kind of semantics is motivated by the fact that it allows one to use probabilities with local meaning, which provides the modularity needed for knowledge representation, similar to the widely used Bayesian networks [10].…”
Section: Introductionmentioning
confidence: 99%